2018
DOI: 10.1039/c8ee00459e
|View full text |Cite
|
Sign up to set email alerts
|

One-of-a-kind: a microporous metal–organic framework capable of adsorptive separation of linear, mono- and di-branched alkane isomers via temperature- and adsorbate-dependent molecular sieving

Abstract: Clean separation of linear, monobranched, and dibranched alkanes is achieved using a flexible, microporous metal–organic framework (MOF).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
96
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 111 publications
(102 citation statements)
references
References 31 publications
(36 reference statements)
3
96
1
Order By: Relevance
“…[13][14][15] Among these fluorescent materials, metal-organic frameworks (MOFs), a class of porous crystalline materials composed of bridged organic linkers and centered metal ions/ clusters, 16 are interesting candidates because the great abundance of functional ligands and metals endow MOFs with very promising physical and chemical properties. [17][18][19][20] Several luminescent MOFs have been used for H 2 S detection in aqueous or real physiological systems. [21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37] Among these explored mechanisms of H 2 S sensing, the "turn-on" effect is the most popular one, where the original non-luminescent MOFs in the "turn-off" state are activated and enhanced upon being exposed to H 2 S. Nitro-functionalized MOFs have been proven to be effective probes for H 2 S detection based on the "turnon" effect.…”
Section: Introductionmentioning
confidence: 99%
“…[13][14][15] Among these fluorescent materials, metal-organic frameworks (MOFs), a class of porous crystalline materials composed of bridged organic linkers and centered metal ions/ clusters, 16 are interesting candidates because the great abundance of functional ligands and metals endow MOFs with very promising physical and chemical properties. [17][18][19][20] Several luminescent MOFs have been used for H 2 S detection in aqueous or real physiological systems. [21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37] Among these explored mechanisms of H 2 S sensing, the "turn-on" effect is the most popular one, where the original non-luminescent MOFs in the "turn-off" state are activated and enhanced upon being exposed to H 2 S. Nitro-functionalized MOFs have been proven to be effective probes for H 2 S detection based on the "turnon" effect.…”
Section: Introductionmentioning
confidence: 99%
“…The newly emerged family of crystalline sorbent materials, metal–organic frameworks (MOFs), holds particular promise for hydrocarbon separation including paraffin/olefin separation in light of their tunable pore size, pore shape, and surface functionality . Long and co‐workers demonstrated that MOFs with open metal sites show favorable adsorption toward olefins over paraffins as a result of a side‐on coordination of olefins at the unsaturated metal centers .…”
mentioning
confidence: 99%
“…Accordingly, we then measured C 6 vapour adsorption at 30 °C and the results were shown in Figure 3e. Ultrahigh n-HEX adsorption capacity up to 209 mg/g was observed, exceeding most top level materials for this task [45][46][47][48][49][50][51][52][53] such as Al-bttotb (151 mg/g), 49 Ca-tcpb (150 mg/g), 48 MIL-53(Fe)-(CF 3 ) 2 (32 mg/g), 47 and Fe 2 (BDP) 3 (113 mg/g) 46 . By contrast, no adsorption and very low adsorption of 10.7 mg/g was observed for the dibranched isomers of 22DMB and 23DMB, owing to MS effect, since the kinetic diameter of dibranched isomers is far larger than the window of [Th 6 Co 2 ] cage.…”
Section: Resultsmentioning
confidence: 94%
“…In the literature, all reports are focused on the separation of C 6 vapour via multicomponent column breakthrough measurements. [45][46][47][48][49][50][51][52][53] From the viewpoint of saving energy, the direct separation of C 6 isomer from liquid mixture is more desirable, as these C 6 isomers are essentially liquid at room temperature with boiling point more than 58°. In each case, the activated Th-Co-Cage-1 samples were rst immersed in commercially binary mixture.…”
Section: Resultsmentioning
confidence: 99%